Fenomena Back Flashover Akibat Sambaran Petir Pada SUTT 150 kV Haurgeulis–Sukamandi#2 - Septian Pramuditia Putra (Elposys: Jurnal Sistem Kelistrikan, 2024)
Lightning disturbances on the 150 kV High Voltage Overhead Transmission Line (SUTT) Haurgeulis-Sukamandi #2 were analyzed to understand their causes and impacts. This study aims to identify and analyze lightning-induced disturbances using data from Fault Locator, Digital Fault Recorder, and Lightning Detection System. The methods used include calculating the protection angle, analyzing the maximum current before shield failure, and applying the Rolling Sphere method. The analysis results showed that the lightning current of -22 kA exceeded the tower’s shielding capacity, causing a Back Flash Over phenomenon that led to system disruption. This finding was confirmed by comparing the measured voltage with the breakdown voltage of the insulator. The implications of this study highlight the importance of enhancing lightning protection systems, such as reducing tower grounding resistance and installing inductance reducers, to prevent similar disturbances in the future. This research provides valuable insights for improving the reliability and safety of power transmission networks in lightning-prone areas.